2023
DOI: 10.1002/gps.5962
|View full text |Cite
|
Sign up to set email alerts
|

The association of pain with suicidal ideation and suicide attempts with depressive symptoms among adults aged ≥50 years from low‐ and middle‐income countries

Abstract: Objectives We aimed to examine the relationship of pain with suicidal ideation and suicide attempts with depressive symptoms among adults aged ≥50 years from six low‐ and middle‐income countries (LMICs) (China, Ghana, India, Mexico, Russia, and South Africa). Methods Cross‐sectional, community‐based, nationally representative data from the WHO Study on global AGEing and adult health were analyzed. Self‐reported information on past 12‐month suicidal ideation and suicide attempts among people with depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have found that compared to other depressed populations (e.g., adolescents), middle-aged adults have more persistent ( 51 ) and severe depressive symptoms ( 52 ), are more difficult to treat ( 53 ), and have depression for a longer period ( 54 , 55 ). This means that most middle-aged adults with depressive symptoms are more likely to develop depression ( 7 ) and that, over time, depressive symptoms will have a greater impact on their physical health ( 52 ), leading to more serious physical illnesses ( 56 ), and may also coexist with chronic illnesses ( 57 ), which may worsen the progression of these illnesses ( 58 , 59 ), increase the risk of self-inflicted suicide ( 60 ), and increase the risk of death ( 61 ). As China is about to enter an aging society, middle-aged and older people will account for an increasing proportion of the current and future Chinese population ( 62 ), with an estimated 500 million people over 80 by 2050 ( 63 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that compared to other depressed populations (e.g., adolescents), middle-aged adults have more persistent ( 51 ) and severe depressive symptoms ( 52 ), are more difficult to treat ( 53 ), and have depression for a longer period ( 54 , 55 ). This means that most middle-aged adults with depressive symptoms are more likely to develop depression ( 7 ) and that, over time, depressive symptoms will have a greater impact on their physical health ( 52 ), leading to more serious physical illnesses ( 56 ), and may also coexist with chronic illnesses ( 57 ), which may worsen the progression of these illnesses ( 58 , 59 ), increase the risk of self-inflicted suicide ( 60 ), and increase the risk of death ( 61 ). As China is about to enter an aging society, middle-aged and older people will account for an increasing proportion of the current and future Chinese population ( 62 ), with an estimated 500 million people over 80 by 2050 ( 63 ).…”
Section: Introductionmentioning
confidence: 99%